2019
DOI: 10.1136/jim-2018-000877
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Radiographic Imaging in Patients with Long Bone Fractures Transferred to a Pediatric Trauma Center

Abstract: This study sought to determine the proportion of children with long bone fractures who undergo duplicate radiographic imaging after transfer to a pediatric trauma center (PTC) for further management. The secondary objective was to explore provider rationale and diagnostic yield of repeat X-rays. This was a single-site, retrospective cohort study conducted at a PTC. All patients, aged 0–21 years, who were transferred to the PTC for management of a long bone fracture were included. Electronic medical records wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Prior literature had emphasized the need for strategies to reduce repeat images in evaluation of pediatric fractures. One retrospective cohort study revealed that 43% of patients who transferred from a referring hospital underwent repeat radiographs, and none of those repeat radiographs provided new or additional diagnoses 15. Therefore, the reduction in repeat imaging at our institution was an extremely promising result, particularly given that there was no evidence to suggest that the additional radiographic images at our institution had greater clinical value than x-rays from external locations.…”
Section: Discussionmentioning
confidence: 88%
“…Prior literature had emphasized the need for strategies to reduce repeat images in evaluation of pediatric fractures. One retrospective cohort study revealed that 43% of patients who transferred from a referring hospital underwent repeat radiographs, and none of those repeat radiographs provided new or additional diagnoses 15. Therefore, the reduction in repeat imaging at our institution was an extremely promising result, particularly given that there was no evidence to suggest that the additional radiographic images at our institution had greater clinical value than x-rays from external locations.…”
Section: Discussionmentioning
confidence: 88%
“…While it was predicted that retakes would drastically reduce when digital images replaced films (due to improved image production), this has not occurred [ 29 , 30 ]. Retakes and rejects are reported to be at the same level (5–12%) now as when films were used [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Waste In Imagingmentioning
confidence: 99%
“…Radiographic imaging, such as plain X-ray, Computed Tomography (CT), and Dual Energy X-ray Absorptiometry (DEXA), are the most common methods for clinical bone diag-nosis, but many studies find that radiography alone offers an incomplete assessment of bone healing and is unreliable in determining the healing stages of bone. [50][51][52] Other drawbacks of radiographic imaging include frequent radiation exposure and high cost, which can be especially detrimental for children, pregnant women, and immune-compromised or ill patients. Recent efforts have focused on developing imageguided therapies that can monitor the host-material interaction of implants, quantitatively assess bone healing, and evaluate the performance of drugs or grafts in a real-time, non-invasive, highly sensitive, and cost-effective way.…”
Section: Introductionmentioning
confidence: 99%